Penerapan Kontrak Kesadaran Diri Untuk Meningkatkan Karakter Disiplin Siswa Kelas X TKR Smk Ma’arif 1 Kretek - Syahid, Nur; Ismail, Ismail (SCAD Independent, 2024)
The school location is close to the market, does not have a canteen and school fence, the parents' weak economic background, low student input causes the level of discipline of class X students of Light Vehicle Engineering SMK Ma'arif 1 Kretek Bantul to be low. The solution to improve students' discipline character is carried out by conducting action research in the form of implementing student self-awareness contracts. The results of implementing self-awareness contracts in the first cycle did not increase students' discipline character because observation and control of contract implementation were once a week. In the second cycle, observation and control of self-awareness contracts were carried out every two days. The result, from the initial condition of 10 alpha students 23 times to 1 alpha student 8 times in the final condition. A total of 4 students skipped school once and no students skipped school in the final condition. The conclusion of this study is that the implementation of self-awareness contracts can significantly improve students' discipline character in attending lessons at school. The suggestion given is that teachers must provide examples and be firm along with guidance on students' self-awareness when implementing disciplinary character education.